Discovery Learning Strategy to Enhance XI Grade MIPA Students' Critical Thinking Abilities regarding Hydrocarone Material in Madrasah Aliyah Laboratorium, Jambi - Nursi, Mat (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
The discovery learning learning strategy is one of the determining aspects in chemistry learning. Chemistry learning at the MA Laboratory is still student-centered. Models and strategies must be collaborative. The research results reveal that the use of the discovery learning model can improve students' thinking skills. The use of the discovery learning model in the learning process for students who have higher intelligence and already have previous knowledge achieve success more quickly with a minimum error of 25.1923%. The use of the discovery learning model for students who have lower intelligence and do not have the prerequisite knowledge can only be done for explanations in understanding concepts, by taking notes, providing guidance in doing exercises and can minimize student errors to a maximum of 28.0385%. The discovery learning model can improve students' thinking skills.